Personal Lineage as the Main Organizational Principle in Daesoon Jinrihoe - Park, Sangkyu (The journal of CESNUR, 2018)
Studies of both traditional and new religions often focus mostly on doctrine. However, East Asian religions, old and new, are oriented to self-cultivation, and exhibit unique organizational features. The article argues that organization is more important than belief to define Korean new religions. The principle of master-disciple personal relationship (yeonwon) was the key organizational principle in Donghak and his successor Cheondoism, Won Buddhism, and the organizations that evolved into Daesoon Jinrihoe, i.e. in the three largest Korean new religions. The three religions, however, interpreted yeonwon differently, and discussed whether the principle derived from divine revelation or simply from the human organizational skills of their founders. Daesoon Jinrihoe reformulated yeonwon, while keeping its basic features, as yeonwun, creating a unique system of personal relationship that may well be the main cause of its phenomenal success and growth.